The therapeutic potential of immunotherapy in the treatment of breast cancer: Rational strategies and recent progress. Issue 4 (26th March 2023) - Javid, Hossein; Attarian, Fatemeh; Saadatmand, Toktam; Rezagholinejad, Nastaran; Mehri, Ali; Amiri, Hamed; Karimi‐Shahri, Mehdi
Abstract: The second leading cause of cancer death in women worldwide is breast cancer (BC), and despite significant advances in BC therapies, a significant proportion of patients develop metastasis and disease recurrence. Currently used treatments, like radiotherapy, chemotherapy, and hormone replacement therapy, result in poor responses and high recurrence rates. Alternative therapies are therefore needed for this type of cancer. Cancer patients may benefit from immunotherapy, a novel treatment strategy in cancer treatment. Even though immunotherapy has been successful in many cases, some patients do not respond to the treatment or those who do respond relapse or progress. The purpose of this review is to discuss several different immunotherapy approaches approved for the treatment of BC, as well as different strategies for immunotherapy for the treatment of BC.